ТАШАББУСКОРЛИК - ТАЛАБА ШАХСИНИНГ ИЖТИМОИЙ АҲАМИЯТЛИ ФАЗИЛАТЛАРИДАН БИРИ СИФАТИДА - Ўрозбоев, Н. (SCIENCE and SOCIETY, 2021)
The article considers initiative as a prerequisite for human development and as a result of education. From the analysis of scientific literature and the results of a number of researchers, the author makes the assumption that initiative is one of the socially significant qualities of a person
Keywords: formation; component; socially significant personality qualities; student; education; initiative; personality